Effect of a microbial inoculant on fermentation characteristics, aerobic stability, intake, and digestibility of corn silage by rams - Rodríguez, Abner A; Acosta, Yunior; Rivera, Viviana; Randel, Paul F (Revista Colombiana de Ciencias Pecuarias, 2016)
ensiling of whole-plant corn in tropical environments generally results in poor fermentation, and silages are susceptible to aerobic deterioration resulting in low acceptability by the animals. Objective: to determine the effect of a microbial additive on ensiling characteristics, aerobic stability, intake and digestibility by rams of diets containing corn silage. Methods: whole-plant corn (Zea mays L. vr. Mayorbella; 38.26% of DM; 3.8-5.0 cm length) was ensiled with or without a microbial starter in 208 L-capacity plastic bags. Triplicate samples of vegetative material were analyzed for pH and fermentation products after 0, 7, 13, 28, and 45 d. Aerobic stability of the fermented forage was determined by measuring increases in pH and temperature after 72 and 96 h, respectively. The DM, CP and NDF intake and digestibility of diets containing the silages were determined using ten crossbred rams. Diets consisted of 50% grass hay and 50% of either inoculated or control silage fed separately. Results: corn fermented with the additive had lower (p < 0.05) pH (3.6 vs. 3.9) and higher (p < 0.05) lactic acid content than untreated silage (1.70 vs. 1.29). Inoculation delayed the aerobic deterioration of the silage as evidenced by lower (p < 0.05) pH and temperature. Intake of DM, CP, and NDF as a proportion of total dietary DM, CP, and NDF consumption increased (p < 0.05), as did CP digestibility (p < 0.05) by 6.20% units, in rams fed hay- treated silage-SBM diets. Conclusions: ensiling tropical corn with the microbial additive enhanced fermentation, delayed aerobic deterioration, and improved dietary CP digestibility by rams.